2022
DOI: 10.1177/02692155211067983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuromuscular electrical stimulation on exercise capacity, muscle strength and quality of life in COPD patients: A Systematic Review with Meta-Analysis

Abstract: Objective To determine the effects of neuromuscular electrical stimulation on disabilities and activity limitation of individuals affected by chronic obstructive pulmonary disease. Data sources MEDLINE, PEDro database, Cochrane Controlled Trials Register, and SciELO, were searched from inception until October 2021. Review methods Inclusion criteria were patients with COPD, randomized controlled trials comparing neuromuscular electrical stimulation alone or combined conventional pulmonary rehabilitation and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Findings from this review suggest that NMES can be a valuable tool for maintaining limb muscle strength during acute exacerbations in patients with COPD, similar to results observed in patients with stable COPD (Alves al., 2022;Hill et al, 2018). Hospitalization due to acute exacerbations can lead to muscle weakness, physical function decline, and exercise capacity decline in patients with COPD (Carr et al, 2009;M.…”
Section: F I G U R Esupporting
confidence: 82%
See 1 more Smart Citation
“…Findings from this review suggest that NMES can be a valuable tool for maintaining limb muscle strength during acute exacerbations in patients with COPD, similar to results observed in patients with stable COPD (Alves al., 2022;Hill et al, 2018). Hospitalization due to acute exacerbations can lead to muscle weakness, physical function decline, and exercise capacity decline in patients with COPD (Carr et al, 2009;M.…”
Section: F I G U R Esupporting
confidence: 82%
“…Neuromuscular electrical stimulation (NMES) is a method used to improve physical function in PR. Some systematic reviews of patients with stable COPD have shown that NMES improves limb muscle strength, exercise capacity, and symptoms of dyspnea (Alves, da Silva E Silva, Martinez, de Queiroz, & Gomes-Neto, 2022;Hill et al, 2018); however, these studies have not focused on the acute exacerbation phase. Gutiérrez-Arias et al investigated the efficacy of NMES in patients with COPD on mechanical ventilatory management (Gutiérrez-Arias et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a specific therapy aimed at improving muscular strength is precisely in line with the peculiarities of CoPd and the demands of patients. Electrical muscle stimulation, on the other hand, is an effective method for preventing muscle atrophy in a variety of populations, including CoPd patients [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The application of Russian current to the expiratory muscles (abdominal muscles) causes phasic contraction, which improves diaphragm strength by forcing the ribs into an oblique and downward position. This gives the diaphragm a mechanical advantage, making contraction easier and decreasing inspiratory flux [21].…”
Section: Introductionmentioning
confidence: 99%